(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Background information: Since the early 1990s, emergency obstetric care (EmOC) in Bangladesh has played important role to reduce the maternal mortality rate. Along with other indicators of improved maternal care, there is a trend of rising caesarean section rates over the last decade affecting the economy of the country. According to demographic and Health Surveys conducted between 1993 and 2004, rate of caesarean section has risen from 2% to 6% which is more pronounced in urban area. Objective: To assess the indications and the trends of caesarean sections done over a 10-year period from 1995- 2004. Study Design: A retrospective observational study of the cases of caesarean sections over a decade. Study setting: Holy Family Red Crescent Medical College Hospital. Results: 23748 women were admitted in department of Obstetrics and Gynacology. Total deliveries were 21149(89.05% of total admission). The caesarean birth rate increased from 45.85% to 70.55%. The indications varied a little in cases of malpresentation and eclampsia. APH and IUGR has risen a little (from 2.56 to 2.6 to 1.83 to 2.34%) respectively. But proportion of repeat caesarean section and that of presumed foetal distress (or less foetal movement) increased (from 25.99 to 31.45% and from 8 to 15%), recently the indication, as maternal choice is also coming up (from .43 to .8%). The proportion has fallen in prolonged labour for cervical dystocia (from 17 to 2.6%) and obstructed labour (from 4.6% to .36%). The data were compared and analyzed by Z Test and corresponding P value was calculated which was not significant. Conclusion: Though caesarean section is a very safe intervention in obstetrics at present, crucial evaluation of the indications is advocated to reduce the rates of caesarean secion. Keywords: Caesarean section rates; Indications DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9432 JBCPS 2011; 29(3): 126-132